Judicialização da saúde: uma questão de limites - Piazenski, Fernando José (2018)
This work proposes a new vision for the judicialization of health, a theme that has a great popular appeal and generated a series of problems for health managers, as it implies budgetary distortions, to escape the normal rules of choice to which all collective decisions that deal policies, as well as for making the beneficiaries of the health system unequal. The research, in the first moment, seeks to expose the reality of the health system and the jurisprudential positioning about the right to medical care, after, to seek the pragmatist consequentialism, the behavioral analysis of the right and the economic analysis of the right, tools that enable an extended view of the subject, insofar as the Brazilian jurist, as a rule, does not worry about possible external effects of decisions - the consequences in the real world. In this work the focus is on the jurist, seeks to demonstrate that concern with consequences external to the law are not part of his daily life. It also seeks to analyze the behavior of the jurist, what its context, what its motivational state and what the consequences that influence the emission of a certain behavioral pattern, in order to explain why the choice of short term solution prevails, in the case, immediate health care, to the detriment of the long-term consequences, a so-called contingency-trap situation.